Accidentes de trabajo: [casi] todos los porqués - Castejón, Emili; Crespán, Xavier (Cuadernos de Relaciones Laborales, 2007)
Work accidents prevention is not an activity that most companies (whose average size is small in all countries) embrace without an external pressure that make it mandatory. That pressure comes from the national preventive systems built up by the governments to force the employers to take care of workers’occupational health and safety. If a national preventive system is well designed and managed work accident rates at the national level evolve following a pattern of slow but continuous diminution, as it happens in most European countries. This is not the case of Spain where accident rates are in the recent years at higher levels than twenty years ago. The different components of Spanish national preventive system are analyzed showing which are the mistakes in its design and/or management.